73.2k views
3 votes
Plz answer fast

Which of the following expressions demonstrates the distributive property?

3 + 4 + 5 = 4 + 3 + 5

-2(5 + 7) = -2(7 + 5)

3(-8 + 1) = 3(-8) + 3(1)

6[(7)(-2)] = [(6)(7)](-2)

User Gelisa
by
4.7k points

2 Answers

4 votes

Answer:

3(-8+1) = 3(-8)+3(1)

Explanation:

HOPETHISHOPES!!

User Epic Speedy
by
5.3k points
4 votes

Answer:

3(-8+1) = 3(-8)+3(1)

Explanation:

you multiply the value(s) in front of the parentheses to the values in them.

User Bdorry
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.